UiTM Unicorn Scholar - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
Congratulations to Nur Hanis Baharudin, a student from Textile Sciences and Fashion Technology programme, on being selected as a participant for UiTM Unicorn Scholar. She will be conducting a project entitled "Embroidery Using Pineapple Yarn (PALF)". UiTM Unicorn Scholar Programme (UiTM USP) is a programme that targets a group of students with outstanding academic performance, excellent leadership, and highly enthusiastic in entrepreneurial activities. This programme is expected to change the landscape of entrepreneurship empowerment throughout the UiTM system including the aspects of cultural entrepreneurship, creating job opportunities, and students' readiness to compete in today's challenging global market.